2010
DOI: 10.29333/ejgm/82889
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physical Activity on Controlling Blood Pressure among Hypertensive Patients from Mishref Area of Kuwait

Abstract: Aim Conclusion:The increased risk of physical inactivity in controlling hypertension in our study suggests that general practitioners must be in the habit of prescribing practice of physical exercise and patients are followed up regularly to confirm that they are adhering to the management plan and the blood pressure targets are being met.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 21 publications
1
21
1
1
Order By: Relevance
“…7 Physical activity (PA) is a cost-effective, practical, natural and effective way of controlling HPT. 2,8 Regular PA is a key component of lifestyle therapy for the primary prevention and treatment of hypertension. 2,8 Studies have demonstrated the beneficial effects of exercise on HPT with reductions in both systolic and diastolic blood pressure with as much as 5-7 mmHg reductions in those with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…7 Physical activity (PA) is a cost-effective, practical, natural and effective way of controlling HPT. 2,8 Regular PA is a key component of lifestyle therapy for the primary prevention and treatment of hypertension. 2,8 Studies have demonstrated the beneficial effects of exercise on HPT with reductions in both systolic and diastolic blood pressure with as much as 5-7 mmHg reductions in those with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In Posbindu PTM activities, members were given counseling about non communicable diseases including hypertension and given special counseling for members suffering from hypertension in detail described hypertension control efforts. According to Alsairafi (2010) the increased risk of physical inactivity in controlling hypertension in our study suggested that general practitioners should be used to prescribe strenuous physical exercise 10 . According to Muhamedhussein (2016) tried to show the level of hypertension and know the risk factors that could explain the high prevalence of hypertension 11 .…”
Section: Knowledge Attitudes and Prevention Behavior Of Ptmmentioning
confidence: 52%
“…Among the study participants, persons who follow sedentary lifestyle (58.16%) were more prone to have uncontrolled blood pressure when compared to persons who follow 9 There was a statistically significant association found between sedentary lifestyle and uncontrolled blood pressure. Similar findings were observed in a study done by Simkhada et al in Nepal.…”
Section: Discussionmentioning
confidence: 73%